Experimental and Numerical Studies on the Seismic Performance of RC Interior Beam-Column Joints. Issue 2 (February 2014) - Meas, Kimreth; Li, Bing; Pham, Thanh Phuong
This paper presents the results from Finite Element (FE) simulation on six Reinforced Concrete (RC) beam-column jointsand experimental study. The joints investigate dhave additional, vertically distributed reinforcement along the beams and lateral cyclic loading is applied, with constant axial force. Experimental results provide insight into the joint behaviour under conventional and unconventional displacement histories in terms of hysteresis loop, crack pattern and joint shear stress. The FE numerical models are validated by comparing the numerical results with experimental results obtained from six tested specimens and two specimens from previous studies. Parametric studies are performed to investigate the complex behaviour of the joints under the influence of axial loads as well as the numbers of vertically distributed reinforcement layers.